Representasi Superego pada Karakter Beruang dalam Kartun Masha and the Bear Episode Tracks of Unknown Animals - Erino, Anggie Putri; Mulyana, Agung Putra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The rapid growth of digital technology has significantly transformed the way children access entertainment, particularly through streaming platforms such as Netflix. One popular animated series, Masha and The Bear, especially the episode “Tracks of Unknown Animals,” presents rich visual symbolism suitable for analysis through a semiotic approach. This study applies Sigmund Freud’s psychoanalytic theory, focusing on the concept of the superego, to examine the character of the Bear, who demonstrates patience, protectiveness, and tolerance toward Masha’s curiosity-driven behavior. The main objective of this research is to reveal how the representation of the superego is embodied through the Bear’s actions and responses in various challenging situations. The semiotic analysis interprets visual signs, expressions, and character interactions within the narrative. The findings indicate that the Bear serves as a moral figure representing the function of the superego in controlling Masha’s impulses and behavior. Therefore, this animated film not only provides entertainment but also conveys moral messages that reflect psychological and educational values for its audience.